ANARKISME BERAGAMA: Tinjauan Paradigma dan Metodologi Pemahaman Ajaran Islam - Agus Afandi; Sjafiatul Mardliyah (AL-TAHRIR, 2014)
Violence in the name of religion is a widespread phenomenon in Indonesia. The question is why such violence occurs and why Muslims are often the perpetrators of religious violence? This article examines these questions from the paradigm and method of understanding Islam. There are various methods in studying Islam promoted by different Muslim groups, such as traditionalists, modernists and post-modernists. There are also many other methods advanced by fundamentalist, apologetic modernist, modernist and secularist Muslims. These methods yield different understanding of Islam, and even more contradictory understanding. To resolve this problem, and to accommodate those various views and uphold tolerance amongst Muslims, a new shifting paradigm is needed. The shift necessitates several steps. The first is validation of all Islamic knowledge. The second is to use a holistic approach to Islam. The third step is an open attitude and willingness to accept religious reform. The forth is a multidimensional approach to Islam and the last is making the objectives of Islamic law as the highest reference in Islamic thoughts. Furthermore, Muslim groups should build up mutual understanding to reconcile and avoid being trapped in an exclusive religiosity.Keywords: religious violence, method, paradigm, holistic principle, reconciliation